Two Versions of Quadratic-Phase Hankel Transformations of Random Order - Roy, Chandra; Kumar, Tanuj; Prasad, Akhilesh; Jha, Govind Kumar (Communications in Mathematics and Applications, 2024)
In this study, we have eliminated the restriction on the remaining parameters for the two versions of quadratic phase Hankel transformations (QPHT) with the aid of a new parameter. Furthermore, the QPHT of random order has been used to solve a few differential equations.